Combined use of tandem mass spectrometry and computational chemistry to study 2H-chromenes from Piper aduncum - Souza, Amauri Alves [UNESP]; Vessecchi, Ricardo; Castro-Gamboa, Ian [UNESP]; Furlan, Maysa [UNESP] (Wiley, 2019)
Natural 2H-chromenes were isolated from the crude extract of Piper aduncum (Piperaceae) and analyzed by electrospray ionization tandem mass spectrometry (ESI-MS/MS) applying collision-induced dissociation. Density functional theory (DFT) calculations were used to explain the preferred protonation sites of the 2H-chromenes based on thermochemical parameters, including atomic charges, proton affinity, and gas-phase basicity. After identifying the nucleophilic sites, the pathways were proposed to justify the formation of the diagnostic ions under ESI-MS/MS conditions. The calculated relative energy for each pathway was in good agreement with the energy-resolved plot obtained from ESI-MS/MS data. Moreover, the 2H-chromene underwent proton attachment on the prenyl moiety via a six-membered transition state. This behavior resulted in the formation of a diagnostic ion due to 2-methylpropene loss. These studies provide novel insights into gas-phase dissociation for natural benzopyran compounds, indicating how reactivity is correlated to the intrinsic acid-base equilibrium and structural aspects, including the substitution pattern on the aromatic moiety. Therefore, these results can be applied in the identification of benzopyran derivatives in a variety of biological samples.
Keywords: benzopyrans; density functional theory; ESI-MS/MS; fragmentation chemistry; quantum chemical calculations